2023
DOI: 10.1136/bmjopen-2022-065230
|View full text |Cite
|
Sign up to set email alerts
|

Does problem-based learning improve patient empowerment and cardiac risk factors in patients with coronary heart disease in a Swedish primary care setting? A long-term prospective, randomised, parallel single randomised trial (COR-PRIM)

Abstract: ObjectivesTo investigate long-term effects of a 1-year problem-based learning (PBL) on self-management and cardiac risk factors in patients with coronary heart disease (CHD).DesignA prospective, randomised, parallel single centre trial.SettingsPrimary care settings in Sweden.Participants157 patients with stable CHD completed the study. Subjects with reading and writing impairments, mental illness or expected survival less than 1 year were excluded.InterventionParticipants were randomised and assigned to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…25 Ensuring that patients are aware of the factors affecting the disease in chronic diseases and empowering them to control the disease leads to positive health outcomes. In particular, using methods such as problem-based learning 31 or self-management empowerment model. 7 that make patients aware of how to reduce risk factors for chronic diseases can provide positive health outcome.…”
Section: Discussionmentioning
confidence: 99%
“…25 Ensuring that patients are aware of the factors affecting the disease in chronic diseases and empowering them to control the disease leads to positive health outcomes. In particular, using methods such as problem-based learning 31 or self-management empowerment model. 7 that make patients aware of how to reduce risk factors for chronic diseases can provide positive health outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, clinical supervisors teach professional knowledge and nursing interns only need to listen, watch, and imitate. Clinical supervisors are active while nursing interns are passive, lacking the capability to stimulate clinical thinking and cultivate their ability to ask questions [5]. The development of nursing students' inherent potential is not given enough attention, which is not conducive to cultivating their comprehensive abilities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional assistance methods include providing relevant dietary advice [ 11 ], diet intervention measures [ 12 ], diet patterns [ 13 ], nutritional supplements [ 14 ], etc. In previous studies, health education related to diet management has been shown to effectively improve the disease awareness of patients with AS and to have a positive impact on some of its indicators, such as blood lipid levels and body mass index [ 15 ]. Before designing interventions, some investigators did not consider whether participants were willing to accept nutritional assistance, and they lacked an understanding of the participants’ daily life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%